A Concentration Phenomenon for p-Laplacian Equation - Yansheng Zhong (Journal of Applied Mathematics)
It is proved that if the bounded function of coefficient Qn in the following equation  -div ⁡{|∇u|p-2∇u}+V(x)|u|p-2u=Qn(x)|u|q-2u,  u(x)=0  as  x∈∂Ω.  u(x)⟶0  as  |x|⟶∞ is positive in a region contained in Ω and negative outside the region, the sets {Qn>0} shrink to a point x0∈Ω as n→∞, and then the sequence un generated by the nontrivial solution of the same equation, corresponding to Qn, will concentrate at x0 with respect to W01,p(Ω) and certain Ls(Ω)-norms. In addition, if the sets {Qn>0} shrink to finite points, the corresponding ground states {un} only concentrate at one of these points. These conclusions extend the results proved in the work of Ackermann and Szulkin (2013) for case p=2.